Operation of a vertical algal biofilm enhanced raceway pond for nutrient removal and microalgae-based byproducts production under different wastewater loadings. (April 2018) - Zhang, Qi; Li, Xuemei; Guo, Dabin; Ye, Ting; Xiong, Meijie; Zhu, Liandong; Liu, Cuixia; Jin, Shiping; Hu, Zhiquan
Graphical abstract: Highlights: Raceway pond was enhanced by algal biofilm and operated at various nutrient loads. The maximum uptake capacity for COD, TN and TP were determined. The chemical composition of the harvested algal biomass was analyzed. Stoichiometric-methane-potential of the system was 21, 471–29, 136 m 3 ·ha −1 ·year −1 . Biodiesel potential of the system was 0.57–1.15 t·ha −1 ·year −1 . Abstract: In this study, a vertical-algal-biofilm-enhanced raceway pond (VAB-enhanced raceway pond) was designed and assessed for wastewater treatment and algal biomass production under different nutrient loading rates. Results indicated that the maximum removal capacity of the system was accordingly 7.52, 6.76 and 0.11 g·m −2 ·day −1 for COD, TN and TP, under which the wastewater effluent concentration could be respectively reduced from 106.00, 92.71 and 1.48 mg/L to 43.5, 11.03 and 0.46 mg/L in continuous mode. Meanwhile, about 7.47–10.10 t·ha −1 ·year −1 of lipid, 14.85–23.01 t·ha −1 ·year −1 of protein and 10.69–14.20 t·ha −1 ·year −1 of carbohydrate could be produced from the algae by the system in large scale. The corresponding estimated stoichiometric-methane-potential and biodiesel production of the harvested biomass was 21, 471–29, 136 m 3 ·ha −1 ·year −1 and 0.57–1.15 t·ha −1 ·year −1, respectively. The findings of this study demonstrate the feasibility of using VAB-enhanced raceway pond for economically and cost-effectively recovery of nutrients from the wastewater via algal-based byproducts production.